Common Defects of Prefabricated Prestressed Elements for Industrial Construction - Rafał Krzywoń; Jacek Hulimka (Buildings, 2024)
This manuscript attempts to classify typical errors occurring during the design, production, and use of prefabricated and prestressed concrete girders and slabs manufactured in Poland for industrial buildings since the 1950s. Although the cases discussed concern Poland, most of them have a universal character, and as such are also found in other countries. The defects and errors are illustrated with examples and the causes of their occurrence are also discussed. A method of classifying flaws based on the period of their occurrence was proposed. Most of the examples discussed were encountered by the authors during their professional work. In most of the presented cases, repair was possible, enabling further safe operation. This paper shows how important it is to periodically check the technical condition of prestressed structures and how common and at the same time trivial mistakes may be made by designers and contractors of this type of structure, despite the experience of over 70 years of their mass use. The quality of modern prestressed structures is undoubtedly higher. Using the experience of previous generations, designers and contractors abandoned the less durable post-tensioned concrete lattice girders. Errors, if they appear, are most often at the stage of implementing new products or are the result of poor workmanship or disregard for unfavorable weather conditions.